2017
DOI: 10.25115/psye.v9i1.465
|View full text |Cite
|
Sign up to set email alerts
|

The relation between math self-concept, test and math anxiety, achievement motivation and math achievement in 12 to 14-year- old typically developing adolescents

Abstract: ABSTRACT:This study examines the relation between math self-concept, test and math anxiety, achievement motivation, and math achievement in typically developing 12 to 14-year-old adolescents (N = 108) from a school for secondary education in the Netherlands. Data was obtained using a math speed test, achievement motivation test, and the math experience questionnaire. A significant positive correlation was found between math self-concept and math achievement in all four math domains (measurement, relations, num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
3
19
0
3
Order By: Relevance
“…It means that the correlation between both variables is positive but low, moreover student self-concept only influenced his/her mathematics procedural knowledge equal to 5.66% and the rest by other variables. This result also equivalents with Timmerman et al (2017) study. According to Andaya (2014), self-directed learning, attitude towards mathematics, motivation, and time spend in learning mathematics were the other factors that can influence students' success in mathematics.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It means that the correlation between both variables is positive but low, moreover student self-concept only influenced his/her mathematics procedural knowledge equal to 5.66% and the rest by other variables. This result also equivalents with Timmerman et al (2017) study. According to Andaya (2014), self-directed learning, attitude towards mathematics, motivation, and time spend in learning mathematics were the other factors that can influence students' success in mathematics.…”
Section: Resultssupporting
confidence: 88%
“…It means students' academic ability influence his/her self-concept. More detail, Timmerman et al (2017) reported that the correlation between math self-concept with math achievement was weak in measurement and relations subject and moderate in numbers and scale subject. He argued that students' attitude and perception about his/her mathematical ability is a main factor of self-concept that influence students' math achievement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the predictive power of the combined independent variables on the outcome variable was strong and significant to show the linear relationship between the five predictor variables and the total variance in senior secondary school students' mathematics achievement. These results are consistent with previous findings (Awofala & Odogwu, 2017;Stankov, Lee, Luo, & Hogan, 2012) in which the relation between mathematics anxiety and mathematics achievement is bidirectional (Carey, Hill, Devine, & Szucs, 2016); mathematics self-concept more strongly relates to mathematics achievement than academic selfconcept (McWilliams, Nier, & Singer, 2013) and mathematics self-concept accounted for a significant unique proportion of variance in mathematics achievement (Timmerman, Toll, & Van Luit, 2017); and that intrinsic and extrinsic motivation play a mediating role in the correlation between academic self-concept and academic achievement in 16 to 19-year-old adolescents (Areepattamannil, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…According to Tully and Jacobs (2010), the gender gap in Mathematics has been an exciting research topic over the decades because the continuous development of technology could affect women's involvement in terms of career and economic opportunities. Mathematics is perceived to be an essential requirement when one pursues mathematically oriented courses such as Science, Engineering, and Technology in college.…”
Section: Introductionmentioning
confidence: 99%